ANALISIS KINERJA ORGANISASI DINAS KEBUDAYAAN DAN PARIWISATA DI MASA PANDEMI COVID-19 (STUDI KASUS UPTD TAMAN BUDAYA RADEN SALEH KOTA SEMARANG) - Hanum Tiastanti; Dyah Hariani; Augustin Rina Herawati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Tourism in Indonesia is currently experiencing an increase, not only for recreational activities but also to improve the economy of a region. The tourist attraction in the city of Semarang is increasing every year, one of which is cultural tourism. UPTD TBRS aims to manage tourism related to arts and culture. This research aims to analyze organizational performance as well as the driving and inhibiting factors of the organizational performance of the Raden Saleh Cultural Park UPTD Semarang City in the Covid-19 Pandemic Period. This research uses descriptive qualitative research methods, data collection techniques through interviews, observations, and documentation. The results showed that the productivity aspect in providing services during the Covid-19 pandemic decreased the effectiveness of the number of visits and the amount of retribution income for UPTD TBRS. The aspect of responsiveness in the form of a complaint container is also still not able to run optimally. The inhibiting factor is the management of human resources related to employee rewards and compensation. The suggestion that researchers can convey is that the Semarang City Culture and Tourism Office together with the head of the UPTD TBRS can increase productivity by completing the construction of multipurpose buildings, updating information on the website, and providing rewards or compensation in the form of money or appreciation.